PENGARUH ARUS DAN WAKTU PADA MICRO RESISTANCE SPOT WELDING TERHADAP BAJA AISI 304 DAN ALUMINIUM PADUAN - Agus Sifa; Mohamad Adib Ichwan; Tito Endramawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Welding is often used in industry as a joining technique, one of which is Micro Resistance Spot Welding (MRSW). MRSW was carried out to know the maximum load and shear stress produced on separate worksheets using AISI 304 and aluminum alloys and then connected using a lap joint. This study uses weld current, weld time, and emphasis on the electrodes. In this, welding is done constantly and does not use cooling. The currents used in welding are 140, 280, and 420 A, then varied with the welding time of 24 ms, 34 ms, and 44 ms and combined with a pressure of 1.3 bar. After welding, the welding results are tested using tensile tests and weldability tests. The results of the study were taken with the highest maximum load on a differentiated worksheet. The highest maximum load is generated at the connection of AISI 304 with AISI 304. In contrast to the connection using aluminum alloys, the resulting load will decrease.